Minor actinide transmutation characteristics in AP1000. (May 2018) - Liu, Bin; Jia, Rendong; Han, Ran; Lyu, Xuefeng; Han, Jinsheng; Li, Wenqiang
Highlights: Too much minor actinide loading amount in AP1000 is meaningless. Loading minor actinide to AP1000 affect the power distribution. FTC and MTC are improved after loading minor actinides to AP1000 reactor. AP1000 incinerate almost 2 times annual minor actinide yield from PWR. Abstract: We study the minor actinide transmutation characteristics by coating different thickness minor actinide on fuel pellets of the AP1000. The calculation results indicate that the more minor actinide is loaded to AP1000, the more boric acid concentration need to be reduced from coolant to let keff return criticality. The relationship between the reduced boric acid concentrations in AP1000 coolant with minor actinide loading amount is not linear. The reduced boric acid concentration in coolant approaches a saturation level after about 300.0 kg minor actinide loading amount. This implies that too much minor actinide loading amount in a single AP1000 fuel loading is meaningless. Our simulation results also denote that loading minor actinide to AP1000 core does affect the power distribution of AP1000 in some way, we need to reduce the boric acid concentration and rearrange the burnable poison rods in the core simultaneously to achieve the purpose of flatting the power distribution. So a moderate minor actinide loading in AP1000 will not adversely affect the core power distribution strikingly. Our calculation results also display that fuel temperature coefficient (FTC) is still negative after adding minor actinide to reactor. In comparison with the standard AP1000 reactor core, the extent of the negative feedback effect of FTC after loading minor actinides is reduced to some extent; the moderator temperature coefficient (MTC) improves the negative feedback effect of the reactor core to a great extent. Taking into account all analytical results about FTC and MTC, the total negative feedback effect on reactor power level changes is improved after loading minor actinides to AP1000 reactor for transmutation. The transmutation rate calculation results show that AP1000 reactor can incinerate 44.0 kg MA nuclides after one year fuel cycle. So AP1000 reactor can incinerate almost 2 times the annual MA yield from a typical PWR reactor.